From dyspnea to Olympic qualification - A case report as a model for post-acute sequelae of COVID-19 - Baudrexl JC; Steinestel K; Gagiannis D (Heliyon)
Introduction: Pulmonary post-acute COVID-19 sequelae (PASC) can occur in professional athletes. In these individuals, the physical impairment can ultimately mean the end of their career due to the lack of specific treatment strategies. Individualised treatment approaches are required, as demonstrated in this case report. Case presentation: Using the example of a female professional athlete, an individualised therapy strategy is outlined step by step on the basis of the assessment of lung function, including spiroergometry, CT imaging and immunocytological and histopathological analysis of bronchoscopically obtained material. This multimodal diagnostic approach was used to identify persistent inflammation without viral persistence and to create an individual treatment plan. In addition to the use of azithromycin and anti-obstructive inhalation therapy, the patient also received three sessions of thermoplasty and a new approach to physiotherapy (myoreflex therapy). This gradually freed the athlete from her restrictions. Over time, she was able to regain her athletic performance, which ultimately led to her successful qualification for the 2024 Summer Olympics in Paris. All objective examination parameters indicated a remission of pulmonary PASC. Discussion: To date, there are no clear treatment recommendations for PASC. The most commonly prescribed treatment regimens often fail to achieve objective success. The present case highlights the need for an individualised diagnostic and therapeutic approach and that complete remission of PASC can be achieved. Based on our findings, multidisciplinary phenotyping of individual cases of pulmonary PASC appears to be of central importance as a basis for an individualised therapeutic approach. It should also be emphasised that the inflammatory processes persist without viral persistence.